Dental findings and special care in patients with Angelman syndrome: a report of three cases. (22nd November 2012) - de Queiroz, Alexandra Mussolino; de Siqueira Melara, Talitha; Fernandes Ferreira, Paula Dariana; Lucisano, Marília Pacífico; De Rossi, Andiara; Nelson‐Filho, Paulo; Bezerra Silva, Raquel Assed
ABSTRACT: Angelman syndrome (AS) is a neurogenetic disorder, characterized by intellectual disability, movement or balance disorders, specific abnormal behaviors, and severe speech and language limitations. Due to its low incidence and the nonspecifity of developmental problems in newborns and young children, AS is not easily identified by clinical pediatricians. The aim of this paper is to present three cases of AS, reporting the orofacial characteristics and requisite dental care in these patients. Interestingly, this investigation found that certain typical features of mouth breathing syndrome, such as long and narrow faces, open mouth, shortened upper lip, lowered mandible position, shadows under the eyes (infraorbital cyanosis), muscular hypotonia, and enlarged and anteriorized tongue, were present in the three studied AS patients.